ВНЕДРЕНИЕ ЭЛЕКТРОННОГО МЕНЕДЖМЕНТА В ПРАКТИКУ ОБРАЗОВАНИЯ - Худайназар Х. Курбанов; Феруза М. Рашидова (International Journal of Innovative Technologies in Social Science, 2019)
The article discusses the actual problems of education - digitalization and the development of electronic management in educational institutions; an information system for collecting data on graduates and their occupation; automation of conducting profiles of teachers and the development of their professional competence; monitoring the academic performance assessment; ensuring transparency and improving the quality of education; implementation of a key performance indicators (KPI).